ANALISIS PENERAPAN KINERJA POSYANDU DI WILAYAH PUSKESMAS HANOPAN KECAMATAN ARSE KABUPATEN TAPANULI SELATAN TAHUN 2020 - Meidiawaty Siregar; Satyawaty Sulubara (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2022)
Integrated Healthcare Centre is form Sourced Health Efforts Community Power that is managed and organized of, by, for, and with community, use empower community and provide convenience in get service health. Destination study this is for knowing performance Integrated Healthcare Centre in the work area public health centre Hanopan District Arse District South Tapanuli. Study this use method quantitative with design cross sectional research. For Study conducted During month January until November 2020. Research results showing that performance Integrated Healthcare Centre working area public health center Hanopan Arse District by whole belong to less. That thing caused by low Integrated Healthcare Centre output component, so that influence acquisition performance Integrated Healthcare Centre . Research results for self-subsistent community, coaching Integrated Healthcare Centre , and participation figure work area community public health center Hanopan Arse District in 2020 in the whole is also included less. Then for the results of statistical tests carried out showing that , from third factor the only self-subsistent community and development Integrated Healthcare Centre that has connection with performance Integrated Healthcare Centre